Profil klinis pasien dengan gejala gangguan motilitas predominan konstipasi di unit endoskopi gastrointestinal rumah sakit tersier - Godfried Erycesar Yeremia Saragih; I Dewa Nyoman Wibawa; I Ketut Mariadi; Gde Somayana (DiscoverSys Inc., 2021)
Background: Investigating constipation requires careful evaluation of general examinations cascaded into specifics to identify treatable or significant causes for early detection. This study aims to determine patients' clinical profile with symptoms of motility disorders, predominantly constipation, in the gastrointestinal endoscopy unit of the tertiary hospital.Methods: This descriptive cross-sectional study involved 82 participants collected through consecutive sampling. Patients with predominant constipation symptoms who underwent colonoscopy in Sanglah Hospital Endoscopy Unit from 2017 to 2018 were recruited. Primary data comprising clinical assessments, laboratory test results, and colonoscopy and histopathology interpretation were analyzed accordingly. Constipation and fecal incontinence severity was indicated by Patient Assessment of Constipation – Symptoms (PAC-SYM) and Jorge-Wexner score. Data was analyzed using SPSS version 25 for Windows.Results: Most of the respondents were male (62.2%). The PAC-SYM and Jorge-Wexner Score were relatively low, with mean values of 2.44±0.73 and 2.18±0.99, respectively. The prevalence of patients initially assessed with chronic constipation (57.32%) remained high (26.83%) despite adjustment being done after colonoscopic exclusion.Conclusion: Diagnostic challenges of constipation exceeded the exhaustive efforts utilizing extensive diagnostic modalities. Suboptimal treatment would be inevitable in the absence of a good-quality management algorithm. Latar Belakang: Investigasi konstipasi memerlukan kecermatan dalam mengevaluasi pemeriksaan umum yang berjenjang menjadi spesifik untuk mengidentifikasi kausa yang dapat ditangani atau bermakna terhadap deteksi dini. Penelitian ini bertujuan untuk mengetahui profil klinis pasien dengan gejala gangguan motilitas predominan konstipasi di unit endoskopi gastrointestinal Rumah Sakit Tersier.Metode: Penelitian deskriptif potong lintang ini melibatkan 82 responden yang dikumpulkan melalui pengambilan sampel secara konsekutif. Pasien dengan gejala dominan konstipasi yang menjalani kolonoskopi di Unit Endoskopi RSUP Sanglah selama tahun 2017 hingga 2018 direkrut. Data primer yang terdiri dari penilaian klinis, hasil tes laboratorium, dan interpretasi kolonoskopi maupun histopatologi dianalisis. Tingkat keparahan konstipasi dan inkontinensia feses ditunjukkan pada skor Patient Assessment of Constipation – Symptoms (PAC-SYM) dan Jorge-Wexner. Data dianalisis menggunakan SPSS versi 25 untuk Windows.Hasil: Sebagian besar atau responden berjenis kelamin laki-laki (62,2%). Skor PAC-SYM dan Jorge-Wexner relatif rendah dengan nilai rata-rata masing-masing 2,44±0,73 dan 2,18±0,99. Prevalensi pasien yang awalnya dinilai dengan konstipasi kronis (57,32%) tetap tinggi (26,83%) meskipun penyesuaian dilakukan setelah eksklusi kolonoskopi.Simpulan: Tantangan diagnostik konstipasi melebihi upaya maksimal dengan memanfaatkan modalitas diagnostik yang luas. Terapi yang kurang optimal tidak dapat dihindari jika tidak ada algoritma manajemen yang berkualitas baik.